Optimizing Chronic Insomnia Care Through Pharmacist Intervention, Laboratory Evaluation, and Administrative Coordination - Shammakhi, Ali Nasser; Mohammed Ali Alhazmi; Ahmed Mohammad Mrair; Yahya Mohammed Dahhas; Adel Hamad Khardli; Abdallah Ali Hakami; Faisal Hassan Al-Harbi; AbualqasimNasser Zoagan; Khaled mossa mashi; NasserMohemmed Mjrshi; et al. (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Chronic insomnia is a highly prevalent sleep disorder characterized by persistent difficulty initiating or maintaining sleep, leading to significant daytime impairment. It is a major public health concern with strong links to psychiatric and medical comorbidities, including depression, anxiety, and cardiovascular disease, and is driven by a complex pathophysiology involving hyperarousal and dysregulation of sleep-wake circuits. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This article aims to outline a comprehensive, interprofessional framework for managing chronic insomnia, emphasizing the synergistic roles of pharmacists, laboratory services, and health administrators in optimizing patient care from diagnosis through long-term treatment. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> The proposed model integrates evidence-based interventions. First-line treatment is Cognitive Behavioral Therapy for Insomnia (CBT-I). Pharmacological options, including GABAergic agents, dual orexin receptor antagonists, and melatonin agonists, are used adjunctively. The framework leverages pharmacists for medication management and deprescribing, laboratory services for identifying underlying medical causes, and health administrators for implementing system-wide protocols and digital health solutions like internet-delivered CBT-I (iCBT-I). <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This collaborative approach facilitates accurate diagnosis, ensures guideline-concordant treatment, and improves patient adherence. It leads to reduced reliance on long-term pharmacotherapy, better management of comorbid conditions, and more efficient use of healthcare resources through streamlined workflows and improved access to first-line behavioral therapies. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Effective management of chronic insomnia requires a unified, systems-based strategy. By integrating the distinct expertise of clinicians, pharmacists, laboratory professionals, and administrators, healthcare systems can shift from a reactive, medication-focused model to a proactive, patient-centered approach that addresses the root causes of insomnia and improves long-term outcomes.